The optimal first-line treatment for patients with left-sided RAS wild-type metastatic colorectal cancer: Double-drug regimen or triple-drug regimen therapy - Cai, Changjing; Luo, Qingqing; Liu, Yihan; Peng, Yinghui; Zhang, Xiangyang; Jiang, Zhaohui; Feng, Ziyang; Qi, Yaru; Gao, Yan; Liu, Yongting; Liu, Ping; Chen, Yihong; et al. (Frontiers in Pharmacology, 2022)
There are many treatments for metastatic colorectal cancer (mCRC). Among them, uncertainty remains especially concerning the clinical benefit of different regimens for left-sided RAS wild-type (WT) mCRC in the triple-drug therapy era. No studies have been conducted to answer this critical clinical issue. We performed a comprehensive analysis of published data and real-world data. First, we conducted analyses of the published trials to show the landscape of efficacy and safety in the treatments of left-sided RAS WT mCRC. Then, we initiated a multicenter real-world study as the validation dataset. This study included six published randomized controlled trials (RCTs) and a total of 1925 patients. The double-drug regimen plus cetuximab/panitumumab (D+C/P) achieved the longest overall survival (OS) in patients with left-sided mCRC (HR=0.74, 95%CI: 0.57-0.98), while triple-drug regimen with bevacizumab (T+B, HR=1.1, 95%CI: 0.63-2.0), compared with double-drug with bevacizumab (D+B). The D+C/P had the highest overall response rate (ORR) in patients with left-sided mCRC (OR=1.8, 95%CI: 0.89-3.8), while T+B (OR=1.8, 95%CI: 0.70-4.8), compared with D+B. The multicenter real-world cohort showed the double-drug regimen plus cetuximab had longer progression-free survival (PFS) in left-sided mCRC patients than the triple-drug regimen with bevacizumab. The safety analysis showed the incidence of the adverse events (grade≥3) in the triple-drug therapy plus bevacizumab was higher than that in the double-drug therapy plus cetuximab/panitumumab. This work demonstrates the ranking of three regimens for therapeutic efficacy and safety in patients with left-sided RAS WT mCRC. The double-drug regimen plus cetuximab/panitumumab appears more effective and safer than double-drug and triple-drug based regimens with bevacizumab. Further trials and cohort analyses on this topic would increase confidence in these results.